What Next for Agriculture After Durban? - Beddington, J.R.; Asaduzzaman, Mohammed; Clark, Megan E.; Fernández Bremauntz, Adrian; Guillou, Marion; Howlett DJB; Jahn, Molly M.; Erda, Lin; Mamo, Tekalign; Negra, Christine; Nobre, Carlos A.; Scholes, Robert J.; et al. (American Association for the Advancement of Science, 2012)
Global agriculture must produce more food to feed a growing population. Yet scientific assessments point to climate change as a growing threat to agricultural yields and food security (1–4). Recent droughts and floods in the Horn of Africa, Russia, Pakistan, and Australia affected food production and prices. The Intergovernmental Panel on Climate Change predicts that the frequency of such extreme weather events will increase (5), which, when combined with poverty, weak governance, conflict, and poor market access, can result in hunger and famine. At the same time, agriculture exacerbates climate change when greenhouse gases (GHGs) are released by land clearing, inappropriate fertilizer use, and other practices (6). Alternative agricultural practices, tailored to different regions, show promise for reducing net GHG emissions and maintaining or improving yields despite extreme weather (7). In Niger, agroforestry on 5 million hectares has benefited >1.25 million households, sequestered carbon, and produced an extra 500,000 metric tons of grain per year (8). In Denmark, agricultural emissions have been reduced by 28%, while productivity increased (9).